Strong and early monkeypox virus-specific immunity associated with mild disease after intradermal clade-IIb-infection in CAST/EiJ-mice - Christian Meyer zu Natrup; Sabrina Clever; Lisa-Marie Schünemann; Tamara Tuchel; Sonja Ohrnberger; Asisa Volz (Nature Communications)
Abstract Monkeypox virus (MPXV) is a zoonotic poxvirus long endemic in West and Central Africa. Outbreaks, first the global spread of clade II outside Africa in 2022, and since 2023 the accelerating spread of clade I in central Africa, point to MPXV adaptations that pose the risk of it becoming more transmissible in humans. Animal models mimicking the clinical disease outcome in humans are important to better understand pathogenesis, host tropism, and the contribution of genetic mutations. Here, we demonstrate that MPXV infection via tail scarification in CAST/EiJ mice is an appropriate animal model to mimic human mpox. In our study, disease outcome is milder in clade IIb than clade IIa-infected mice, which is associated with enhanced immunogenicity early during infection. This suggests that clade IIb more efficiently activates host immune responses, highlighting how this animal model could facilitate studying new MPXV variants to help develop efficient antivirals and preventive measures.